Coating small-diameter ePTFE vascular grafts with tunable poly(diol-co-citrate-co-ascorbate) elastomers to reduce neointimal hyperplasia. (6th April 2021) - Yu, Lu; Newton, Emily R.; Gillis, David C.; Sun, Kui; Cooley, Brian C.; Keith, Andrew N.; Sheiko, Sergei S.; Tsihlis, Nick D.; Kibbe, Melina R.
Abstract : We report the need to develop POCA elastomers as ascorbate-based surface coating to modify the luminal surface of small-diameter ePTFE grafts in order to overcome graft occlusion induced by neointimal hyperplasia. Abstract : Lack of long-term patency has hindered the clinical use of small-diameter prosthetic vascular grafts with the majority of these failures due to the development of neointimal hyperplasia. Previous studies by our laboratory revealed that small-diameter expanded polytetrafluoroethylene (ePTFE) grafts coated with antioxidant elastomers are a promising localized therapy to inhibit neointimal hyperplasia. This work is focused on the development of poly(diol- co -citrate- co -ascorbate) (POCA) elastomers with tunable properties for coating ePTFE vascular grafts. A bioactive POCA elastomer (@20 : 20 : 8, [citrate] : [diol] : [ascorbate]) coating was applied on a 1.5 mm diameter ePTFE vascular graft as the most promising therapeutic candidate for reducing neointimal hyperplasia. Surface ascorbate density on the POCA elastomer was increased to 67.5 ± 7.3 ng mg −1 cm −2 . The mechanical, antioxidant, biodegradable, and biocompatible properties of POCA demonstrated desirable performance for in vivo use, inhibiting human aortic smooth muscle cell proliferation, while supporting human aortic endothelial cells. POCA elastomer coating number was adjusted by a modified spin-coating method to prepare small-diameter ePTFE vascular grafts similar to natural vessels. A significant reduction in neointimal hyperplasia was observed after implanting POCA-coated ePTFE vascular grafts in a guinea pig aortic interposition bypass graft model. POCA elastomer thus offers a new avenue that shows promise for use in vascular engineering to improve long-term patency rates by coating small-diameter ePTFE vascular grafts.